2004
DOI: 10.1080/1356251042000252372
|View full text |Cite
|
Sign up to set email alerts
|

Self‐efficacy and statistics performance among Sport Studies students

Abstract: The present study explored predictive paths between performance accomplishments, self-ef®cacy, and performance among Sport Studies students taking a Level 1 statistics module. Fifty-eight Level 1 Sport Studies undergraduate degree students completed a 44-item self-ef®cacy measure and an assessment of perceived academic success at the start of the module. Self-assessed worksheets taken in weeks 4 and 5 were used as a second performance measure. Self-ef®cacy was re-assessed in week 7 and students handed the assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
22
1
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 16 publications
9
22
1
5
Order By: Relevance
“…Lastly, the relationships documented among self-efficacy, anxiety, and performance are consistent with past findings. There is a consistent negative relationship reported between statistics anxiety and course performance (Onwuegbuzie & Wilson, 2003), and evidence of a positive relationship between self-efficacy and performance (Lane, Hall, & Lane, 2004). Our finding of a strong negative relationship between anxiety and self-efficacy supports past findings (Onwuegbuzie, 2000;Pajares & Miller, 1995), and it has been suggested that poor self-efficacy beliefs in the face of learning statistics may create a selffulfilling prophecy for students (Perepiczka, Chandler, Becerra, 2011).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Lastly, the relationships documented among self-efficacy, anxiety, and performance are consistent with past findings. There is a consistent negative relationship reported between statistics anxiety and course performance (Onwuegbuzie & Wilson, 2003), and evidence of a positive relationship between self-efficacy and performance (Lane, Hall, & Lane, 2004). Our finding of a strong negative relationship between anxiety and self-efficacy supports past findings (Onwuegbuzie, 2000;Pajares & Miller, 1995), and it has been suggested that poor self-efficacy beliefs in the face of learning statistics may create a selffulfilling prophecy for students (Perepiczka, Chandler, Becerra, 2011).…”
Section: Resultssupporting
confidence: 81%
“…Overall, students enjoyed the specific techniques used (M = 5.33, SD = 1.62), felt it was worthwhile to participate in such a study (M = 5.24, SD = 1.73), and were very satisfied with the statistics course (M = 6.57, SD = .68) with all means significantly above the midpoint of the scale (ps < .001). Correlations (see Table 4) were also examined between the averaged ratings of anxiety and self-efficacy and final course grade to determine if our results were in line with previous findings (Lane, Hall, & Lane, 2004;Onwuegbuzie, 2000;Onwuegbuzie & Wilson, 2004). A non-significant negative relationship between anxiety and performance was observed whereas a marginally significant positive relationship between self-efficacy and course performance existed.…”
Section: Main Analysessupporting
confidence: 60%
See 1 more Smart Citation
“…The results of the study reported in this article, concerning the importance of purpose, variety and novelty, extend the understanding of this topic that can be currently derived from the literature. Failing to see the purpose in subject-based sessions has not been commonly reported in the transition or retention literature, but is more commonly apparent within certain aspects of study skills such as the teaching of statistics (Lane et al, 2004). The relatively favourable findings of the current study in relation to all categories of learning environment also extend existing research on transition programmes.…”
Section: Discussionsupporting
confidence: 70%
“…Curzon (2004) suggests that the students, the subject matter, resources and constraints should all be considered before preparing a formal teaching session. Where possible, the subject being taught should relate to the experiences, interests and expectations of the students since this allows them to better understand the practical implications of the 9 theories being taught and enhances student enthusiasm (Dewar, 2002;Lane, Hall, & Lane, 2004). Teaching strategies that encourage discussion are often more effective in fostering retention and transfer of knowledge to problem solving situations (Horgan, 1999).…”
Section: A Teachermentioning
confidence: 99%